Advancing 5G communication systems: a novel method for OOBE suppression in Filter-OFDM waveforms - Falih, Ammar Ahmed; Ahmad Anas, Siti Barirah; A. Rasid, Mohd Fadlee; Hanafi, Marsyita (Engineering and Technology Publishing, 2025)
Today’s 5th Generation (5G) wireless communications systems count heavily on Orthogonal Frequency Division Multiplexing (OFDM) waveforms. Numerous concerns regarding OFDM-based Long-Term Evolution (LTE) communication limitations have not been thoroughly explored. In contrast, Out-of-Band Emissions (OOBE) occur when a signal is transmitted or received outside the accessible frequency range and poses a problem. This situation is a significant obstacle to creating state-of-theart 5G communication technology. Some thoughts have been given to modifying the OFDM filters for 5G communications due to their resistance to Inter Carrier Interference (ICI) and Inter Symbol Interference (ISI). To reduce spectral leakage into neighbouring sub-bands, OFDM-based waveforms require pulse windowing. This paper proposes a Kaiser-Blackman A (KBA) filter that shows Key Performance Indicators (KPIs) in the simulation concerning OOBE with minimal complexity. The filter was observed in the Power Spectrum Density (PSD) of the Adjacent Channel Leakage Ratio (ACLR) in the time domain, yielding a result of –170 dBm, which was then measured in the frequency domain at –180 dBm. Comparatively, –220 dBm shows an improvement in performance in the hybrid domain, unlike conventional filters’ baseline performance. As a result, low latency has been achieved, which is considered a critical challenge of 5G communication and beyond.